(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Human life is closely connected with the plant world. During its evolutionary development, the human body reliably adapted to proteins, carbohydrates, fats and a wide variety of biologically active substances (vitamins, macro and microelements, organic acids, etc.) of plant origin, without which the normal course of life processes and the development of the body as a whole is impossible. As a result of this symbiosis, some plants eventually began to serve humans as food, others as medicine. One of these plants is saffron. The article reflects the chemical composition and medicinal properties of the main types of fruits and vegetables common in our diet. They can be called differently: food for the healthy, medicine for the sick, a priceless gift of nature, a green or home pharmacy.